Abrasive Wear Resistance of High-Strength Compacted Graphite Iron under Microabrasion Conditions - Daniela Wollmann; Maria Angélica de Miranda; Giuseppe Pintaude (Lubricants, 2022)
Compacted graphite iron (CGI) has been considered an excellent option for heavy-duty engine blocks due to its superior mechanical properties, which allow reduction of weight, enhancing engine performance. Abrasion is a recognized wear mechanism in engine blocks, meaning it deserves to be evaluated for CGI. This study analyzed two grades of high-strength CGI (GJV450 and GJV500) submitted to microscale abrasion tests in free ball configuration using two different slurries: diamond and silica. There was more wear to the surfaces tested with silica due to the particle size, which was one order of magnitude larger than the diamond. The data obtained showed that both materials presented similar resistance when tests were performed with the diamond slurry. On the other hand, when silica was used, GJV500 presented 2.5 times greater wear resistance than GJV450, even though its global hardness was only 17% greater.